The Effect of Price Perception, Product Quality and Location on Consumer Purchase Decisions Through Buying Interest As Intervening Variables on MSME Products During The Covid-19 Pandemic - Sengkey, Yuliana Marce; Mandey, Silvya L.; Soegoto, Agus Supandi (European Journal of Life Safety and Stability (2660-9630), 2021)
In Indonesia, one of the main priorities in national economic development is the existence of Micro, Small and Medium Enterprises (MSMEs). Regional economic activities are mostly supported by activities originating from micro, small and medium enterprises as evidenced by the existence of small household-based businesses. The purpose of this study is to analyze the effect of price perception on buying interest, to analyze the effect of product quality on buying interest, to analyze the influence of location on buying interest, to analyze the effect of price perception on purchasing decisions, to analyze the effect of product quality on purchasing decisions, to analyze the influence of product quality on purchasing decisions. analyze the influence of location on purchasing decisions, to analyze the effect of buying interest on purchasing decisions. This research method is a quantitative research method. The research was conducted at UD. Mandiri UMKM, Pangu 1 Village, East Ratahan District, Southeast Minahasa Regency. Research respondents were 61 respondents. The distribution of the questionnaires was done online using Google Form. Data analysis used path analysis with SPSS. The results showed that Price Perception had a Positive and Significant effect on Purchase Intention but had no effect on Purchase Decision. Product quality has no effect on Purchase Interest and Purchase Decision. Location has a positive and significant effect on Purchase Interest and Purchase Decision. Purchase intention has no effect on Purchase Decision. Southeast Minahasa Regency. Research respondents were 61 respondents. The distribution of the questionnaires was done online using Google Form. Data analysis used path analysis with SPSS. The results showed that Price Perception had a Positive and Significant effect on Purchase Intention but had no effect on Purchase Decision. Product quality has no effect on Purchase Interest and Purchase Decision. Location has a positive and significant effect on Purchase Interest and Purchase Decision. Purchase intention has no effect on Purchase Decision. Southeast Minahasa Regency. Research respondents were 61 respondents. The distribution of the questionnaires was done online using Google Form. Data analysis used path analysis with SPSS. The results showed that Price Perception had a Positive and Significant effect on Purchase Intention but had no effect on Purchase Decision. Product quality has no effect on Purchase Interest and Purchase Decision. Location has a positive and significant effect on Purchase Interest and Purchase Decision. Purchase intention has no effect on Purchase Decision. The results showed that the price perception had a positive and significant effect on purchase intention but had no effect on purchasing decisions. Product quality has no effect on Purchase Interest and Purchase Decision. Location has a positive and significant effect on Purchase Interest and Purchase Decision. Purchase intention has no effect on Purchase Decision. The results showed that the price perception had a positive and significant effect on purchase intention but had no effect on purchasing decisions. Product quality has no effect on Purchase Interest and Purchase Decision. Location has a positive and significant effect on Purchase Interest and Purchase Decision. Purchase intention has no effect on Purchase Decision.